DIVERSE STRESS TREATMENTS AND ACINETOBACTER BAUMANNII PERSISTER FORMATION - Wedean. G. A.,; S.S. Mahmood,; Z.F. Mahmood, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate diverse stress treatments on Imipenem susceptible A. baumannii for persister cells formation. Isolates were assessed for persister cells presence by colony forming unit counting (CFU/ml) after exposure to Imipenem (10 µg/ml) in presence and absence of acid stress treatment (pH 6) for 0-7 hr. In- vitro activity of curcumin to synergize Imipenem to kill persister cells was investigated. The frequency of hicAB and relEB of type II toxin- antitoxin (TA) loci was evaluated by polymerase chain reaction. The transcription level of hicA and relE toxin genes was assessed by quantitative reverse transcriptase polymerase chain reaction. The level of persistence varied between isolates and across the stress conditions. Imipenem treated isolates gave persister fraction of 0.07% to 0.4% whereas Imipenem + pH6 treated isolates gave 0.3% to 0.7% of the initial untreated population. No significant reduction in persistence level was observed after combination with curcumin (P value > 0.05). The hicAB and relEB loci were detected in 100% and 61.5% of Imipenem susceptible isolates, respectively. Imipenem triggered hicA toxin gene transcription while acid stress triggered hicA and relE toxin genes transcription in persister cells.